Measuring the economic value of data and cross-border data flows A business perspective - Nguyen, David (OECD Digital Economy Papers, 2020)
The amount and variety of data that companies collect, aggregate and analyse has increased dramatically in recent years. This paper investigates how the economic value of data can be conceptualised and measured from a business perspective. It discusses data monetisation as a strategy for developing new business models or enhancing traditional ones, and proposes a new taxonomy for data that focuses on measuring its business value. The paper also discusses how different data characteristics and types affect economic value, before examining the role of cross-border data flows as a key enabler of our global economy. As part of this discussion, the concept of a "global data value chain" is presented, based on the idea that digitalisation enables the physical detachment of data collection, analysis, storage and monetisation. The paper concludes with a summary and discussion of the most promising avenues for measuring the economic value of data